A Systematic Literature Review on Corporate Tax Planning - Haervi Yunira; Tengku Eka Susilawaty; Sambas Ade Kesuma; Iskandar Muda (International Journal of Social Service and Research, 2023)
An overview of the evolution of tax planning research is the goal of this study. Corporate tax planning, or the capacity of the corporation to plan its tax affairs, refers to the use of a variety of techniques to legally lower its tax bills or to take advantage of tax law gaps. The narrative method of reviewing the literature is used in this work, and it entails compiling and synthesising previously published studies on corporate tax planning. The information was gathered from publications by American Accounting Association, Emerald, Elsevier, Inderscience, Taylor and Francis Ltd. that were published in international journals that were indexed by Scopus. Samples from 2010 to 2022 included up to 33 articles about corporate tax planning. Many empirical studies use a quantitative approach by showing that by utilizing transfer pricing with agency theory, corporate tax planning performance can be measured.